Integrative Structural Investigation on the Architecture of Human Importin4_Histone H3/H4_Asf1a Complex and Its Histone H3 Tail Binding. Issue 6 (16th March 2018) - Yoon, Jungmin; Kim, Seung Joong; An, Sojin; Cho, Saehyun; Leitner, Alexander; Jung, Taeyang; Aebersold, Ruedi; Hebert, Hans; Cho, Uhn-Soo; Song, Ji-Joon
Abstract: Importin4 transports histone H3/H4 in complex with Asf1a to the nucleus for chromatin assembly. Importin4 recognizes the nuclear localization sequence located at the N-terminal tail of histones. Here, we analyzed the structures and interactions of human Importin4, histones and Asf1a by cross-linking mass spectrometry, X-ray crystallography, negative-stain electron microscopy, small-angle X-ray scattering and integrative modeling. The cross-linking mass spectrometry data showed that the C-terminal region of Importin4 was extensively cross-linked with the histone H3 tail. We determined the crystal structure of the C-terminal region of Importin4 bound to the histone H3 peptide, thus revealing that the acidic patch in Importin4 accommodates the histone H3 tail, and that histone H3 Lys14 contributes to the interaction with Importin4. In addition, we show that Asf1a modulates the binding of histone H3/H4 to Importin4. Furthermore, the molecular architecture of the Importin4_histone H3/H4_Asf1a complex was produced through an integrative modeling approach. Overall, this work provides structural insights into how Importin4 recognizes histones and their chaperone complex. Graphical Abstract: Highlights: The C-terminal region of Importin4 extensively interacts with the N-terminal tail of histone H3. The crystal structure of the C-terminal region of Importin4 with a histone H3 peptide shows that histone H3 binds to the acidic patch in Importin4. Histone H3 K14 is the primary residue interacting with Importin4. Asf1a modulates the binding of histone H3/H4 to Importin4. The molecular architecture of the Importin4_Histone H3/H4_Asf1a complex was produced through an integrative modeling approach that combined X-ray crystallography, cross-linking mass-spectrometry and negative-stain electron microscopy data.